The contribution of personal and place-related attributes to the resilience of conflict-affected communities. (December 2020) - Shapira, Stav; Cohen, Odeya; Aharonson-Daniel, Limor
Abstract: This study explores the associations between personal and place-related attributes and their associations with community resilience among individuals exposed to continuous traumatic stress. A cross-sectional survey was conducted among 1001 adults residing adjacent to the Gaza border in southern Israel (Mage = 53, SD = 16.5 years; 70% were female). The results identified vulnerable individuals and groups in terms of risk of experiencing a decrease in resilience levels, as well as related risks and protective factors. Specific life roles (parenthood), family-related concerns, and lack of social support were negatively associated with community resilience. The person-place connection was identified as a strong explanatory variable of community resilience and as a possible protective factor against the adverse consequences of continuous exposure to traumatic stress. Highlights: Place-related social attributes and social support were strong explanatory variables for community resilience. Age <40, family-related concerns, and specific life roles (parenthood) were negatively associated with community resilience. PTSD levels were relatively low among the participants. The people-place connection offers a possible path for creating a safety net for populations facing communal stressors.